A new surgical approach of direct perineal wound full‐thick closure for perineal wound of abdominoperineal resection for rectal carcinoma: A prospective cohort trial. Issue 6 (4th August 2020) - Yang, Yong‐Ping; Yu, Ling‐Yun; Wang, Min; Mu, Yu; Li, Jian‐Nan; Shang, Feng‐Jia; Wu, Xian‐Feng; Liu, Tong‐Jun; Shi, Jian
Abstract: Perineal wound complications after APR have high morbidity in the colorectal surgical department. Although some approaches have been figured out to solve this clinical focus, the outcomes are still not satisfied. Herein, this prospective comparative clinical trial has been designed to evaluate a new surgical procedure of direct perineal wound full‐thick closure (DPWC), compared with conventional perineal wound closure (CPWC), with hopes of making wound healing with less complications. In addition, an evaluation of an incision negative wound pressure therapy, as another focus in this field, was also analysed in the DPWC group. A total of 44 participants in our department were recruited from March 2018 to March 2020, divided into two groups randomly, CPWC group and DPWC group. The patients' characteristics, such as age, gender, BMI, smoking, alcohol consumption, comorbidities, CEA level, and high‐risk of invasion, were recorded without statistical significance between the CPWC group and DPWC group. After the same standard abdominal phase, these two groups were performed in different perineal phases. And then, operative and postoperative outcomes were analysed with different statistical methods. Data on wound healing time and length of stay in the DPWC group were shorter than those in the CPWC group ( P  < .05). Furthermore, cases of wound infection within 30 days in the DPWC group were also less than that in the CPWC group ( P  < .05). However, no difference was found between the incisional negative pressure wound therapy assisted group (NPA group) and non‐ incisional negative pressure wound therapy assisted group (non‐NPA group). During this study, hypoalbuminemia, as an independent high‐risk factor, impacted perineal wound healing. ( P = .0271) In conclusion, DPWC is a new surgical approach, which can lead to a better outcome than DPWC, and it can be another surgical procedure for clinicians. In addition, hypoalbuminemia should be interfered for avoiding perineal wound complications.